GOOD CORPORATE GOVERNANCE MECHANISMS IN MEASURING QUALITY OF FINANCIAL STATEMENTS AND TRANSFER INVESTOR LEVELS - Syafrida Hani; Hafsah UMSU (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
ABSTRACTThis study aims to develop a theory of determining the quality of financial statement reports that can increase investor confidence in financial information presented by management. This research would like to find the role of good corporate governance in improving the quality of financial statements as measured by accounting conservatism and earnings management, then it will be seen how the quality ability of financial statement can influence investor confidence level. The result of the research did not find the influence of corporate governance mechanism on the quality of financial statements. However, the simultaneous test results found that corporate governance mechanisms and the quality of financial statements affect the level of investor confidence. Profit management as an indicator of the quality of financial statements negatively affects the level of investor confidence. But accounting conservatism declared no effect on the level of investor confidence. The results of the test with path analysis found that the variables that have a direct influence of the mechanism of good corporate governance is the ownership of the institution, while other variables have no influence either directly or indirectly.